Telmatobius solitarius n. sp.: A New Rare Telmatobiid Frog from the Highland Patagonian Territories (Rio Negro, Argentina) - Cei, José Miguel Alfredo María (1970)
Telmatobius solitarius, a new rare species from the ancient volcanic tableland of Southern Pilcaniyeu (Rio Negro, Argentina), is described. Its general relationships with the recently discovered Telmatobius praebasalticus and T. reverbera are discussed. The general features of such a chain of semiterrestrial telmatobiid frogs from the highland Patagonian territories are pointed out.